2017
DOI: 10.19044/esj.2017.v13n21p98
|View full text |Cite
|
Sign up to set email alerts
|

Diversité Et Variabilité Du Régime Alimentaire Des Éléphants Du Parc National d’Azagny (Sud - Côte d’Ivoire)

Abstract: In Côte d'Ivoire, Azagny National Park has a small forest elephants population, described as isolated, self-contained and whose survival depends on the diversity of local biological resources. A study was undertaken to assess the diversity of the plant species consumed and the feeding preference of this large mammal. Pedestrian surveys were carried out in the different biotopes traveled by the elephants during one year, in search of fresh and old traces of nutrition and droppings. As a result of these inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The organs of tree species, especially shrubs, are the most consumed by elephants. Similar observations were made by Kouamé et al [25] . In contrast, research conducted by Mbété et al [27] in the Democratic Republic of Congo revealed that lianas are the species most consumed by elephants.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The organs of tree species, especially shrubs, are the most consumed by elephants. Similar observations were made by Kouamé et al [25] . In contrast, research conducted by Mbété et al [27] in the Democratic Republic of Congo revealed that lianas are the species most consumed by elephants.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the vegetation of the TNP is dense evergreen forest, providing leafy twigs are available almost yearround. The results of this study are similar to those carried out by Blake [29] in Central Africa and Mbété et al [25] in Congo's Ogooué Lékéti National Park on the nature of the forest elephant's diet. Apart from leafy twigs, fruit is the second most important component in elephants' diets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation